Marked Seasonal Variation in Structure and Function of Gut Microbiota in Forest and Alpine Musk Deer - Jiang, Feng; Gao, Hongmei; Qin, Wen; Song, Pengfei; Wang, Haijing; Zhang, Jingjie; Liu, Daoxin; Wang, Dong; Zhang, Tongzuo (Frontiers in Microbiology, 2021)
Musk deer (Moschus spp.) is a globally endangered species due to excessive hunting and habitat fragmentation. Captive breeding of musk deer can efficiently relieve the hunting pressure, and contribute to the conservation of wild population and musk supply. However, its effect on the gut microbiota of musk deer is unclear. Recent studies have indicated that gut microbiota is associated with host health and its environmental adaption, influenced by many factors. Herein, high-throughput sequencing of the 16S rRNA gene was used based on 262 fecal samples from forest musk deer (M. berezovskii) (FMD) and 90 samples from alpine musk deer (M. chrysogaster) (AMD). We sought to determine whether seasonal variation can affect the structure and function of gut microbiota in musk deer. The results demonstrated that FMD and AMD had higher α-diversity of gut microbiota in the cold season than in the warm season, suggesting that season change can affect gut microbiota diversity in musk deer. Principal coordinates analysis (PCoA) also revealed significant seasonal differences in the structure and function of gut microbiota in AMD and FMD. Particularly, phyla Firmicutes and Bacteroidetes significantly dominated the 352 fecal samples from captive FMD and AMD. The relative abundance of Firmicutes and the ratio of Firmicutes to Bacteroidetes were significantly decreased in summer than in spring and substantially increased in winter than in summer. In contrast, the relative abundance of Bacteroidetes showed opposite results. Furthermore, dominant bacteria genera and main metabolic functions of gut microbiota in musk deer showed significant seasonal differences. Overall, the abundance of main gut microbiota metabolic functions in FMD was significantly higher in the cold season. WGCNA analysis indicated that OTU6606, OTU5027, OTU7522 and OTU3787 were at the core of the network and significantly related with the seasonal variation. These results indicated that the structure and function in the gut microbiota of captive musk deer vary with seasons, which is beneficial to the environmental adaptation and the digestion and metabolism of food. This study provides valuable insights into the healthy captive breeding of musk deer and future reintroduction programs to recover wild populations.